Comparative determinations of trace and minor elements in coral aragonite by ion microprobe analysis, with preliminary results from Phuket, southern Thailand - Allison, N. (Geochimica et cosmochimica acta, 1996)
The ion microprobe technique was developed for semiquantitative analysis of trace and minor elements in coralline aragonite. The size of the microprobe beam (ca. 30 μm diameter) allows an examination of the spatial geochemical heterogeneity of coral skeletons on a much finer scale than has previously been possible. Of the elements investigated magnesium, calcium, rubidium, strontium, barium, and uranium appeared suitable for analysis under the operating conditions used although it was not possible to unequivocally confirm that 85Rb and 238U were not subject to molecular interferences. A homogenous carbonate standard was only available for magnesium so some relative ion yields were calculated using a standard silicate glass. Magnesium, rubidium, strontium, and barium concentrations were in reasonable agreement with previously reported values. Uranium concentrations were considerably lower, probably reflecting a miscalibration of the ion microprobe. Reproducibility of analysis was investigated by comparing immediately adjacent pairs of analyses on coral material. Although analytical accuracy was questionable, precision was good and concentration differences between samples reflect true variations in geochemistry. High resolution time series analyses of magneisum, rubidium, strontium, barium, and uranium in Porites lutea corals indicated that the aragonite was heterogeneous on a small spatial scale (over distances attributed to less than one month's skeletal growth). This heterogeneity does not appear to reflect expected variations in seawater temperature or chemistry. It may reflect the metal binding capacity of a heterogeneous organic matrix unevenly distributed throughout the coral skeleton. Individual coral colonies deposited substantially different ranges of Mg and Ba, within and between reef sites, which could lead to significantly different seawater:coral distribution coefficients being calculated between individuals of the same coral species.